PROBLEMATIKA PESANTREN SEBAGAI LEMBAGA PENDIDIKAN ISLAM DI INDONESIA - PS, Alaika M Bagus Kurnia (Tawazun: Jurnal Pendidikan Islam, 2019)
The aim of Islamic education as Ahmad Tafsir's opinion is to humanize humans. Islamic education must guide students in their development, both physical and spiritual towards the formation of the main personality which is based on Islamic laws. But over time, Islamic education is no longer as rich as its history, Islamic education today, has suffered many setbacks due to several factors. Islamic education is not free from problems that arise in the current era. Pesantren as an Islamic educational institution is also not immune to various problems that arise in the global era. Islamic boarding schools as traditional Islamic educational institutions in Indonesia play an important role in preserving and developing Islamic sciences. In addition, pesantren play a role in shaping the characteristics of Indonesian Muslims. During the New Order, pesantren competed with schools recognized by the government. In addition, modern human life patterns also influence the existence of pesantren as traditional Islamic educational institutions. To maintain its existence, the pesantren made a number of changes that were considered necessary, but still preserved the traditions of the past. This paper will discuss various problems faced by pesantren in the global era. Abstrak Tujuan pendidikan Islam sebagai mana pendapat Ahmad tafsir adalah untuk memanusiakan manusia. Pendidikan Islam harus membimbing siswa dalam perkembangan mereka, baik secara fisik maupun spiritual terhadap pembentukan kepribadian utama yang didasarkan pada hukum Islam. Namun seiring berjalannya waktu, pendidikan Islam tidak lagi sekaya sejarahnya, pendidikan Islam saat ini, telah mengalami banyak kemunduran karena beberapa faktor. Pendidikan Islam tidak bebas dari permasalahan yang muncul di jaman ini. Pesantren sebagai institusi pendidikan Islam juga tidak kebal terhadap berbagai permasalahan yang muncul di era global. Pesantren sebagai lembaga pendidikan Islam tradisional di Indonesia memainkan peranan penting dalam melestarikan dan mengembangkan ilmu keislaman. Selain itu, pesantren berperan dalam membentuk karakter Muslim Indonesia. Selama Orde Baru, pesantren berkompetisi dengan sekolah yang diakui pemerintah. Selain itu, pola kehidupan manusia modern juga mempengaruhi keberadaan pesantren sebagai lembaga pendidikan Islam tradisional. Untuk mempertahankan keberadaannya, pesantren membuat sejumlah perubahan yang dianggap perlu, namun tetap melestarikan tradisi masa lalu. Makalah ini akan membahas berbagai masalah yang dihadapi pesantren di era global.